THU0498 PAIN RELIEF AND GAIN OF FUNCTION FROM LOW DOSE RADIOTHERAPY FOR EPICONDYLITIS, FINGER OSTEOARTHRITIS AND PLANTAR FASCIITIS – RESULTS OF A PROSPECTIVE CLINICAL TRIAL. (June 2019) - Eberle, Brigitte; Rogers, Susanne; Vogt, Debroah; Meier, Elisabeth; Moser, Lorenz; Gomez, Silvia; Desborough, Susanne; Takacs, Istvan; paul, Hasler; Bodis, Stephan
Abstract : Background: Low dose radiotherapy (LDRT) is an effective treatment for therapy-resistant musculoskeletal disorders that is associated with only minimal toxicities and low costs [1]. As the population in many countries ages and such disorders result in significant impairment in quality of life and costs, there is now a wider international interest in LDRT for these conditions [2]. Numerous retrospective series describe the benefits of LDRT for non-malignant joint disorders, with response rates between 63-89% [3], but randomized and prospective data are scarce, [4, 5, 6]. Objectives: To prospectively evaluate pain, function and quality of life after low dose radiotherapy (LDRT) in patients with lateral and medial epicondylitis (LE and ME), finger osteoarthritis (OA) and plantar fasciitis (PlF). Methods: Patients over 40 years old were recruited to this single center trial. LDRT (8 x 0.5 Gy, 200 kV X-rays) was repeated once up to a total dose of 8.0 Gy. Pain scores (visual analogue scale=VAS), function tests and quality of life questionnaires were documented at 0, 2, 6, and 12 months. Results: 204 sites were treated. At 12 months after last LDRT (first or second course) compared with baseline prior to first LDRT: 39 LE sites reported pain reduction (median change in VAS) at rest (-2.5, p<0.001), during activity (-6.0, p<0.001) and increase in handgrip strength (median change: extension 16 kg, p<0.001, flexion 5.2 kg, p=0.002). 10 ME sites showed pain relief at rest (-3.0, p=0.041), during activity (-0.4, p=0.041) and an increase in handgrip strength (6.5 kg, p=0.022). 99 finger OA sites reported significant pain relief during activity (-3.0, p<0.001) with a trend at rest (0.0, p=0.056) and gain in handgrip strength (2.5 kg, p=0.004) with a trend to stronger pinch grip (0.5 kg, p=0.099). 56 PlF sites reported reduction in pain scores at rest (-4.0, p<0.001), during activity (-6.0, p<0.001) and an improvement in the walking test (-5.0 seconds, p<0.001). A trend towards improved quality of life was seen in patients with ME and PlF. Conclusion: Patients with LE and ME, finger OA and PlF achieved sustained analgesia and an objective improvement in musculoskeletal function 12 months after completion of LDRT with 4-8 Gy. References: [1] Keilholz L et al. Radiotherapy for painful degenerative joint disorders. Indications, technique and clinical results. Strahlenther Onkol 1998;174:243-250. [2] Taylor RE et al.Radiotherapy for benign disease: Current evidence, benefits and risks. Clin Oncol 2015;27:433-435. [3] Seegenschmiedt MH et al. Radiotherapy for non-malignant disorders: State of the art and update of the evidence-based practice guidelines. Br J Radiol 2015;88:20150080. [4] Ott OJ et al. Radiotherapy for calcaneodynia. Results of a single center prospective randomized dose optimization trial. Strahlenther Onkol 2013;189:329-334. [5] Prokein B et al. Radiotherapy of painful heel spur with two fractionation regimens : Results of a randomized multicenter trial after 48 weeks' follow-up. Strahlenther Onkol 2017;193:483-490. [6] Niewald M et al. German Cooperative Group on Radiotherapy for Benign Diseases of the German Society for Radiation O. Randomized, multicenter trial on the effect of radiation therapy on plantar fasciitis (painful heel spur) comparing a standard dose with a very low dose: Mature results after 12 months' follow-up. Int J Radiat Oncol Biol Phys 2012;84:e455-462. Disclosure of Interests: None declared